Gender constancy and genital knowledge in Filipino preschool children - Dy, M. R. (2003)
In line with the Piaget's conservation concepts and Kohlberg's work on gender constancy, a study was conducted among Filipino pre-schoolers to determine the development of their gender constancy and determine the relationships between gender constancy and genital knowledge. Age and gender differences were also determined. The 87-preschoolers, aged 3-5 years old, from three laboratory school completed the following tests: the own-gender constancy test, other gender constancy test, and the genital knowledge test. For own-gender constancy, sex was a significant variable. The mean score or male pre-schoolers was higher than female pre-schoolers. For other gender constancy, age was a significant variable. There was a difference in mean scores across the three age groups. There was a positive but low correlation between own-gender constancy and other-gender constancy scores. This relationship was also observed for other-gender constancy and genital knowledge.
Keywords: Preschool children